The Influence of Motivation Self-Efficacy and Job Market Considerations on Students' Interest in a Career in Taxation - Putri, Rizqia Amanda; Juitania, Juitania (Darul Yasin Al Sys, 2025)
This study aims to analyze the influence of Motivation, Self Efficacy and consideration of the job market against the career interest of students in taxation. The sample used in this study was 128 students universitas pamulang. The sample used in this study is primary data in the form questionnaires to of distributing questionnaires to students of universitas pamulang which has been used as a research sample. The variable used in study are Motivation (X₁), Self Efficacy (X₂) and consideration of the job market (X₃) as the independent variable. The career interest of students in taxation (Y) as dependent variable. Multiple regression method is used as a research methodology in this study. Analysis of the results of the study used SPSS 26 software. The result of study Motivation, Self Effication and consideration of the job market against the career interest of students in taxation.